(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In the article, the author examines the development of the service sector in the context of digital changes in Uzbekistan. The author explores the problem from the point of view of the introduction of digitalization achievements. Relevant recommendations are being developed as part of the study.